Juridical Analysis of the Causes of the Issuance of Certificates of Management Rights on Land With Property Rights Certificates: Analisis Yuridis Mengenai Sebab-Sebab Terbitnya Sertifikat Hak Pengelolaan Atas Tanah Bersertifikat Hak Milik - Mohammad Saleh; Suhadi Suhadi (Annual Review of Legal Studies, 2024)
Land is a very vital asset for every person and country. When viewed from the physical and value aspects of the soil, it is certainly a thing that has economic and political value in it. Problems that arise in the soil in Indonesia have been a very long time even since the time of the Netherlands because of its high value, problems often arise. For example, the Jepara Regency Government with its citizen named Tanto Untung and his heir Tanto Santoso has even reached the Court with Decision Nomo 19/Pdt.G/2020/PN Jepara. This research is carried out by means of qualitative research using a sociological juridical or empirical juridical approach. The sources used are primary and secondary sources obtained from observations, interviews, documentation and also literature studies. The results of this study show that there is a way of land acquisition carried out by the Jepara Regency Government that is known to the holder of the Certificate from which the land claim originated. The existence of two rights that exist on a piece of land without legal clarity is referred to as a double certificate. The registration of management rights processed by the Jepara Land Office which produced the management right certificate Number 6 of 1998 Jobokuto on behalf of the Jepara Regency Government without taking into account whether the land has or not causes an overlap of rights in the future. The heirs who do not know the land boundary are also a problem that the court decision by the Jepara Land Office cannot be implemented in accordance with the Minister of Agrarian Affairs Number 21 of 2020 concerning the Handling and Settlement of Land Cases, the Jepara Land Office by implementing the decision Number 19/Pdt.G/2020/PN Jpa